ELECTRODEPOSITION OF NICKEL COATING ON AA7075 SUBSTRATE VIA MODIFIED SINGLE ZINCATING METHOD WITH ASSISTANCE OF COPPER ACTIVATION - Othman, I.S.; Starink, M.J.; Wang, S.C. (Journal of Advanced Manufacturing Technology (JAMT), 2020)
The established single zincating procedure leads to non-homogenous zinc deposition rendering the surface incompatible for successive electrodeposition, due to low adhesion between coating and the substrate. A combination of single zincating with copper activation was employed on an aluminium alloy 7075 (AA7075) substrate at prolonged zincating duration so as to incapacitate the shortcomings of the conventional single zincating process. Copper activation was applied to suppress the high dissolution of substrate in the highly alkaline solution during zincating process. The time-transition curve of open circuit potential (EOC) were recorded to study the dissolution of substrate in zincating solution. The composition and surface morphology of AA7075 substrate from copper activation procedure at diverse range of duration were distinguished by energy dispersive X-ray analysis (EDX) and scanning electron microscopy (SEM). The progression of surface morphology of substrates was distinguished by characteristics pertaining to Atomic Force Microscopy (AFM) and SEM. The analysis of the coating adhesion of nickel deposits in the presence and absence of copper activation was conducted by a scratch tester. The adhesion breakdown of coating created from a single zincating process at 1 minute is diminished by the copper activation method. As reflected in the SEM results, the copper activation produces uniform size of zinc deposits and improves their distribution on the substrate. With prolonged zincating duration, there is sufficient time for the zinc deposits to growth and finally covered the whole surface without reveal the substrate. These results contributes to the uniform deposition of nickel coating, thus contribute to the improvement in the coating adhesion.